Functions of p120-catenin in physiology and diseases - Jin, Xin; Lin, Ting; Wang, Yunjuan; Li, Xiaoqian; Yang, Yanhong (Frontiers in Molecular Biosciences, 2024)
p120-catenin (p120) plays a vital role in regulating cell-cell adhesion at adherens junctions, interacting with the juxtamembrane domain (JMD) core region of E-cadherin and regulates the stability of cadherin at the cell surface. Previous studies have shown significant functions of p120 in cell-cell adhesion, tumor progression and inflammation. In this review, we will discuss recent progress of p120 in physiological processes and diseases, and focus on the functions of p120 in the regulation of cancer and inflammation.